Religious America, Secular Europe? A Theme and Variations - Bruce, Steve (Sociology of religion, 2010)
This slim volume is a useful compendium of contrasting observations about religion in Europe and the United States. Peter Berger introduces it with a succinct summary of major contrasts, and then Grace Davie and Effie Fokas fill in the detail with discussions of contrasting histories, differing intellectual traditions, institutional carriers, demographic differences in religious adherence, and policy implications. Each chapter contains sensible summaries of major issues such as the impact of state churches, the class correlates of religion, differences in education and legal systems, and the gender difference in religious commitment. Experts will find little new here, but newcomers will find it instructive and it is sufficiently well written that European and U.S.